THE IMPACT OF COVID-19 ON THE ECONOMY, HEALTH, AND POVERTY IN PROVINCE OF WEST NUSA TENGGARA - Sriningsih, Siti; Suriadi, Irwan; Fatimah, Siti; Salmah, Emi; ,Bq.Saripta Wiji Mulawiani, ,Bq.Saripta Wiji Mulawiani5 (CV. Radja Publika, 2022)
The Covid-19 pandemic that has occurred since March 2020 has affected all aspects of life. The purpose of this study is to describe the impact of the pandemic in terms of health, economy, and poverty in districts/cities in West Nusa Tenggara (NTB) Province. The results of the study are (1) The impact of the COVID-19 pandemic on health aspects is the high number of positive cases and deaths; high positive cases occur in areas that are centres of economy and government; (2) This COVID-19 pandemic causes a decrease in economic growth, and economic slowdown causes unemployment. However, the economic structure of West Nusa Tenggara Province is supported by the construction and service sectors which still show positive growth during the pandemic; (3) The social impact of the COVID-19 pandemic is represented by an increase in poverty in every Regency/City in West Nusa Tenggara, poverty occurs in areas that have a high number of unemployed and positive for COVID-19. The implication for the province of NTB is to encourage programs handling poverty alleviation, health, and increasing economic growth, especially in spending on economic and health functions.